A comparative study of planar 3-RRR and 4-RRR mechanisms with joint clearances. (August 2016) - Zhang, Xuchong; Zhang, Xianmin
Abstract: This paper presents a comparative study of the fully actuated 3-RRR mechanism and the redundantly actuated 4-RRR mechanism. The joint clearances are taken into consideration in both kinematic and dynamic analysis of the two mechanisms. In the kinematic analysis, the joint clearance is treated as a mass-less virtual link, and the error transfer equations of these mechanisms are obtained by the first derivation of the constraint equations. In the dynamic analysis, the joint clearance is fully described and the dynamic equations of the two mechanisms are derived using the Newton–Euler method. The dynamic equations are solved by using the two-step Bathe integration method. The results indicate that the 4-RRR mechanism shows better performances in both kinematics and dynamics when compared with the 3-RRR mechanism. Highlights: The redundant and regular planar 3DOF mechanisms with joint clearances are compared. Clearances influence the kinematics and dynamics of mechanisms significantly. The redundant mechanism shows better performance than the non-redundant one.